Preliminary surveillance of Japanese encephalitis virus in mosquito Culex species in the West Peninsular Malaysia - Amir, M.E.; Yasmin, A.R.; Syafiqah, I.; Tijani, K.A.; Natasha, J.A.; Arshad, S.S.; Mustaffa-Kamal, F.; Nur-Fazila, S.H.; Hassan, S.S.; Ahmad-Khusaini, M.K.S. (Malaysian Veterinary Medical Association, 2024)
Japanese encephalitis virus (JEV), a mosquitoes-borne virus primarily spread by Culex mosquitoes, and the infection is capable of causing a significant public health concern particularly in Malaysia. By collecting mosquitoes from two distinct sites namely migratory bird areas and pig farms, this study aimed to employ molecular screening of JEV by using reverse transcription-polymerase chain reaction (RT-PCR). These localities were selected based on their association with JEV reservoirs and dynamics of transmission. Results indicated no evidence of JEV was detected in any of the collected mosquitoes. Absence of JEV infection in the area suggests low prevalence and necessity to prolong the study timeframe and extend the locality. This study emphasises the need for constant surveillance on the aspect of epidemiology and ecological factors influencing the dynamics of JEV transmission in Malaysia.